2022
DOI: 10.1097/tp.0000000000004157
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 and Liver Transplant: How Has It Behaved in This Sixth Wave?

Abstract: Background. Since the declaration of a new variant of concern (VOC), Omicron, by the World Health Organization in November 2021, a quick spread has been documented worldwide, being the main VOC in the sixth wave in Spain. The Omicron variant has more transmissibility, lower virulence, and less risk of severe disease than previously described VOC. Here we analyze the current wave of severe acute respiratory syndrome coronavirus 2 infection in liver transplant recipients (LTRs). Methods. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…However, 11.2% of LTR with breakthrough infections still required hospitalization for COVID-19-associated complications despite fulfilling the recommended vaccination status. These results are in line with mortality (2–10%) and hospitalization rates (3–56%) that were found in SOT [ 25 , 36 , 37 , 38 ] and a small Spanish single-center study that included 30 LTR with a hospitalization and mortality rate of 3.3% [ 25 ].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…However, 11.2% of LTR with breakthrough infections still required hospitalization for COVID-19-associated complications despite fulfilling the recommended vaccination status. These results are in line with mortality (2–10%) and hospitalization rates (3–56%) that were found in SOT [ 25 , 36 , 37 , 38 ] and a small Spanish single-center study that included 30 LTR with a hospitalization and mortality rate of 3.3% [ 25 ].…”
Section: Discussionsupporting
confidence: 86%
“…Whether the various subvariants lead to different clinical courses is not well known yet, and contradicting results were reported by different research groups [ 22 , 23 , 24 ]. There are only limited data available on the severity of the clinical course of COVID-19 [ 25 ], frequency of the development of long-lasting symptoms, and immune response in LTR with breakthrough infections during the Omicron wave.…”
Section: Introductionmentioning
confidence: 99%
“…53 Meanwhile, in the sixth wave of the epidemic, family transmission became the main mode of infection (intra-family transmission [17/30; 56.6%], intra-hospital transmission [6.6%]). 60,76 As time goes by, LT's activities are proceeding in an orderly manner. One positive SARS-CoV-2 LT in a patient with acute liver failure due to Wilson crisis has been successfully performed, and other studies have shown that LT surgery in positive patients can be performed after safety assessment.…”
Section: Acetaminophenmentioning
confidence: 99%
“…However, it is a dangerous situation for decompensated LT patients remaining at home and lacking care 53 . Meanwhile, in the sixth wave of the epidemic, family transmission became the main mode of infection (intra‐family transmission [17/30; 56.6%], intra‐hospital transmission [6.6%]) 60,76 . As time goes by, LT's activities are proceeding in an orderly manner.…”
Section: Influence Of Liver Disease To Covid‐19mentioning
confidence: 99%